High incidence of hip and knee arthroplasty in former professional, male football players - Volpi, P.; Quaglia, A.; Carimati, G.; Petrillo, S.; Bisciotti, G. N. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: The purpose of this study was to estimate the incidence of hip and knee arthroplasty in Italian male professional football (soccer) players who have played for a minimum 10 years in the Italian major football leagues. METHODS: The study group was formed by 104 male professional football players who were interviewed to evaluate the incidence of hip and knee arthroplasty. The data were collected through a questionnaire and the results collected were compared with a control group of 100 volunteers matched for age, weight and height, who did not present orthopedic diseases but had never practiced sport. RESULTS: In the study group, 26 subjects (25%) underwent hip and knee arthroplasty at an average mean age of 62.1±6 years. The frequency of arthroplasty was: 13.5% for the hip, 5.8% for the knee and 5.8% for both hip and knee. In the control group, the incidence of arthroplasty was 1% for the knee and no subjects presented hip arthroplasty. CONCLUSIONS: Italian male, former professional football players present a higher than normal incidence of hip and knee arthroplasty. Further studies are necessary to understand the pathological pathways underlying the etiology of hip and knee osteoarthritis in male populations of former professional football players in order to develop effective preventive programs to reduce the percentage of arthroplasties.